Piotra Choynowskiego „Rzeczy drobne i zabawne” - Kochanowski, Marek (Sztuka Edycji, 2021)
Rec.: P. Choynowski, Rzeczy drobne i zabawne, oprac. A. Stańczak, red. M. Gabryś-Sławińska i A. Wójtowicz, Wydawnictwo UMCS, Lublin 2019.